Slovenian Freight Forwarding After the Accession to the EU - Jakomin, Igor; Medeot, Marino (Promet - Traffic&Transportation, 2004)
The moment the Republic of Slovenia joins the EU all theservice offices or agencies related to cross-border operations, inparticular the freight fmwarders, will feel the consequences reflectingthese issues, or resulting therefrom:- In the field of legislation, no major direct consequences areexpected, but rather some indirect ones;- Bigger freight forwarders, better provided with capital andpresent globally will affect the operations arising from thechanged market position in the common European logisticalmarket;- As result of market changes, certain adverse financial effectswill occur in some forwarders. This will affect the social positionof employees as well;- The consequences in the macro-economic level will notonly reflect on the social area, but also on lower newlyadded value, and on some non-exploited part of the capital.The facts listed above show that the accession of Sloveniato the EU will bring about a series of adverse consequences inall freight forwarders in the first stage. The economic consequenceswill be mainly visible in the decrease of revenues offreight forwarders, whereas the social outcome will reflect in redundancies.These will lead to closing-down, liquidation orbankruptcy of minor freight forwarding agents.